Giant Mediastinal Teratoma - Balci, Akin Eraslan; Ayan, Erhan; Ozalp, Koray; Duran, Mehmet; Vuraloglu, Sadik (Bilimsel Tip Publishing House, 2006)
We want to share our experience on a giant mediastinal teratoma diagnosed in a patient who applied with hemoptysis. A 26 years old male patient applied to our clinic with complaints of cough, shortness of breath and hemoptysis of approximately 100 ml/day for the last 20 days. A smoothly lobulated mass with heterogen density suggesting fat tissue, which originated from the right anterior mediastinum was documented at thoracic CT scan. The thorax was explorated from the 6th intercostal space with a posterolateral thoracotomy incision. A 12x14 cm dimension of mediastinal mass reaching from the azygos vein level on the above to the dome of diaphragm on the below, becoming atelectasis because of compression on to the right lung's upper, middle and lower lobes in the exploration. The result of the pathophysiologic examination was reported as immature teratoma containing muscle, immature cartilage, nervous and fat tissues. It is different from classical suggestions, mediastinal teratoma is a possible cause of hemoptysis despite of no relationship with bronchial tree. It can also make way to compression atelectasis. The mass was removed successfully despite late diagnosis and giant dimensions with surgical intervention.
Keywords: giant mediastinal teratoma; hemoptysis; surgical treatment